2003
DOI: 10.1007/s00299-003-0621-x
|View full text |Cite
|
Sign up to set email alerts
|

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants

Abstract: Taro bacilliform virus (TaBV) is a pararetrovirus of the genus Badnavirus which infects the monocotyledonous plant, taro ( Colocasia esculenta). A region of the TaBV genome spanning nucleotides 6,281 to 12 (T1200), including the 3' end of open reading frame 3 (ORF 3) and the intergenic region to the end of the tRNA(met)-binding site, was tested for promoter activity along with four different 5' deletion fragments (T600, T500, T250 and T100). In transient assays, only the T1200, T600, T500 fragments were shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Constitutive promoters identified from plant viruses, such as the Cauliflower Mosaic Virus (Odell et al, 1985;Kay et al, 1987;Benfey & Chua, 1990;Holtorf et al, 1995;Wilmink et al, 1995), Cassava Vein Mosaic Virus (Verdaguer et al, 1998), Figwort Mosaic Virus (Sanger et al, 1990;Maiti et al, 1997;Bhattacharyya et al, 2002), Peanut Chlorotic Streak Virus (Maiti & Shepherd, 1998;Bhattacharyya et al, 2003), Taro Bacilliform Virus (Yang et al, 2003), Cestrum Yellow Leaf Curling Virus (Stavolone et al, 2003), Mirabilis Mosaic Virus (Dey & Maiti, 1999), Sugarcane Bacilliform Badnavirus (Tzafrir et al, 1998;Schenk et al, 1999Schenk et al, , 2001 and Subterranean Clover Stunt Virus (Schunmann et al, 2003) are widely used in biotechnology. This is in part due to a scarcity of well characterized strong constitutive plant promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive promoters identified from plant viruses, such as the Cauliflower Mosaic Virus (Odell et al, 1985;Kay et al, 1987;Benfey & Chua, 1990;Holtorf et al, 1995;Wilmink et al, 1995), Cassava Vein Mosaic Virus (Verdaguer et al, 1998), Figwort Mosaic Virus (Sanger et al, 1990;Maiti et al, 1997;Bhattacharyya et al, 2002), Peanut Chlorotic Streak Virus (Maiti & Shepherd, 1998;Bhattacharyya et al, 2003), Taro Bacilliform Virus (Yang et al, 2003), Cestrum Yellow Leaf Curling Virus (Stavolone et al, 2003), Mirabilis Mosaic Virus (Dey & Maiti, 1999), Sugarcane Bacilliform Badnavirus (Tzafrir et al, 1998;Schenk et al, 1999Schenk et al, , 2001 and Subterranean Clover Stunt Virus (Schunmann et al, 2003) are widely used in biotechnology. This is in part due to a scarcity of well characterized strong constitutive plant promoters.…”
Section: Introductionmentioning
confidence: 99%
“…These include the various enhanced 35S promoters from the dicot-infecting DNA Cauliflower mosaic virus (CaMV) [13] or the promoters of monocot-infecting DNA viruses like Rice tungro bacilliform virus (RTBV) [14, 15], Commelina yellow mottle virus [16], Taro bacilliform virus [17], Banana streak virus (BSV) [18], and Sugarcane bacilliform virus (SCBV) [19, 20]. Viral promoters derived from monocot-infecting DNA viruses are of particular interest because they tend to confer a tissue-specific gene expression, specifically in the vascular system [14, 1620].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic engineering of banana plants has recently proven to be a useful alternative method for the introduction of new desirable traits. Although still labor-and time-consuming, several studies have reported the development of transgenic bananas with enhanced disease tolerance against weevil (Kiggundu et al 2003) and nematodes (Atkinson et al 2004), but to a higher extent it transgenic bananas have been recently used as a model system to study the expression of both plant and viral regulatory sequences (Dugdale et al , 2001Hermann et al 2001;Schenk et al 1999;Yang et al 2003). Previous papers and reviews have discussed the advantages of using chitinases for plant protection because these enzymes are fungicidal, part of the plant defense system, and non-toxic to plants, animals, and higher vertebrates.…”
Section: Discussionmentioning
confidence: 98%